Ionic liquid grafting modified high-temperature-resistant bio-based nylon as well as preparation method and application thereof
Through ionic liquid graft modification technology, the crystallinity and thermal properties of nylon 5T are improved, the problem of insufficient crystallinity is solved, and high-strength, high-oriented, and high-crystalline bio-based nylon is achieved, which improves its processing stability and spinning performance.
Patent Information
- Application Number
- CN202411676789.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
AI Technical Summary
The crystallinity of nylon 5T is insufficient, which affects its heat resistance, strength and dimensional stability, making it difficult to perform thermoplastic processing.
By prepolymerizing and final polymerization of bio-based nylon salts with imidazole ionic liquids, ionic liquid grafting modified high-temperature resistant bio-based nylon is formed, which reduces the intermolecular force, increases the molecular chain spacing, and improves thermal properties and crystallization behavior.
It improves the strength, orientation and crystallinity of biomass nylon, enhances its processing stability and spinning performance, and reduces energy consumption.
Smart Images

Figure BDA0005147234940000151
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of bio-based polymer materials, and in particular to an ionic liquid graft-modified high-temperature-resistant bio-based nylon and a preparation method and application thereof. Background Art
[0002] High temperature resistant nylon refers to special nylon that can be used in a temperature environment above 150°C for a long time. It is also the earliest thermoplastic material used in the aerospace field and has become an indispensable part of the aviation material field. In addition to the excellent properties of ordinary nylon, high temperature resistant nylon has more outstanding heat resistance. The glass transition temperature T m Generally, it is between 280 and 350°C, and can be made into various heat-resistant connectors and weather-resistant and creep-resistant antenna covers in aircraft or spacecraft. Bio-based high-temperature resistant nylon 5T is a kind of high-temperature special nylon product, which is obtained by polymerization of phthalic acid and bio-based pentamethylenediamine. Due to the presence of aromatic rings with good heat resistance in the main chain of the molecule and the ability to form hydrogen bonds, it has higher strength, rigidity and dimensional stability than aliphatic nylon. Its melting point is about 370°C, which is close to the decomposition temperature of nylon. It has thermal decomposition before it melts and cannot be processed by thermoplastic molding. A third monomer is often introduced for copolymerization to lower its melting point, so that it has excellent thermal stability during processing, so that it can be extruded and injection molded.
[0003] However, the crystallinity of nylon 5T needs to be further improved. The crystallinity and morphology of polymers have an extremely important influence on the heat resistance, strength, dimensional stability, etc. of the material. Improving the crystallinity of polymers is the key to obtaining high-quality nylon 5T products. In nylon polymers, adjacent molecular chains are connected to each other by hydrogen bonds. In order to maximize hydrogen bonds, different nylon molecular chains will have different arrangements during the formation of hydrogen bonds, resulting in different crystal structures (α-type and γ-type). Fatty acid nylon chains are highly flexible, and the molecular chains can be linked to form a stable α crystal structure through hydrogen bonding forces. For semi-aromatic odd-even nylon 5T polymers, the large number of aromatic ring structures on the molecular chain makes its mobility poor, and the macromolecular chains cannot be completely arranged in a plane zigzag shape. In order to maximize hydrogen bonds, the hydrogen bond planes will be arranged in a certain orientation, thus forming a relatively imperfect crystallization γ-type structure. Summary of the invention
[0004] The purpose of the present invention is to provide an ionic liquid grafted modified high temperature resistant bio-based nylon and a preparation method and application thereof. The prepared ionic liquid grafted modified high temperature resistant bio-based nylon has the characteristics of high strength, high orientation and high crystallinity.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing ionic liquid graft-modified high-temperature-resistant bio-based nylon, comprising the following steps:
[0007] mixing a bio-based nylon salt with water, mixing the obtained salt solution with an additive, and performing a prepolymerization reaction to obtain a prepolymer;
[0008] The prepolymer is mixed with an imidazole ionic liquid to carry out a polymerization reaction to obtain an ionic liquid graft-modified high-temperature-resistant bio-based nylon.
[0009] Preferably, the bio-based nylon salt includes semi-aromatic bio-based nylon salt and / or aliphatic bio-based nylon salt; the semi-aromatic bio-based nylon salt includes nylon 5T salt and / or nylon 5I salt; the aliphatic bio-based nylon salt includes one or more of nylon 54 salt, nylon 56 salt and nylon 510 salt; the mass fraction of the bio-based nylon salt in the salt solution is 30 to 90%.
[0010] Preferably, the additive includes one or more of a catalyst, an antioxidant, an antistatic agent, a weathering agent, a capping agent, a nucleating agent, a flame retardant and a matting agent; the mass of the additive is 0.01 to 2.2 wt.% of the mass of the salt solution.
[0011] Preferably, the prepolymerization reaction is carried out at a temperature of 200 to 240° C., a pressure of 1.5 to 2.3 MPa, and a time of 0.5 to 5 h.
[0012] Preferably, the anion of the imidazolium ionic liquid includes one of a halogen ion, an inorganic acid ion, a carboxylate ion and a sulfonate ion; the cation of the imidazolium ionic liquid includes one of a binary substituted imidazolium cation, a ternary substituted imidazolium cation and a quaternary substituted imidazolium cation.
[0013] Preferably, the halogen ion is a fluoride ion, a chloride ion or a bromide ion; the inorganic acid ion includes a sulfate ion, a hydrogen sulfate ion, a carbonate ion, a phosphate ion, a dihydrogen phosphate ion, a dihydrogen phosphate ion, a borate ion, a nitrate ion, a hexafluorophosphate ion or a tetrafluoroborate ion; the carboxylate ion includes an acetate ion, a propionate ion or a butyrate ion; the sulfonate ion includes a methanesulfonate ion, a toluenesulfonate ion or a trifluoromethylsulfonate ion;
[0014] The anions of the imidazole ionic liquid also include diethyl phosphate ions, ethyl sulfate ions, ethyl sulfonate ions, bis(2,4,4-trimethylpentyl)phosphinate ions, bis(trifluoromethanesulfonyl)methane ions, bis(malonate)borate ions, bis(pentafluoroethyl)phosphinate ions, tetrakis(methylsulfate)borate ions or bis(salicylate)borate ions;
[0015] The dibasic substituted imidazolium cation includes 1,3-dimethylimidazolium cation, 1-butyl-3-methylimidazolium cation, 1-ethyl-3-methylimidazolium cation, 1-octyl-3-methylimidazolium cation, 1-allyl-3-methylimidazolium cation, 1-butyl-3-ethylimidazolium cation, 1-benzyl-3-methylimidazolium cation, 1-dodecyl-3-methylimidazolium cation, 1-hexadecyl-3-methylimidazolium cation, 1-eicosyl-3-methylimidazolium cation, N-methylimidazolium cation, N-butylimidazolium cation or N-dodecylimidazolium cation;
[0016] The ternary substituted imidazolium cation includes 1,2,3-trimethylimidazolium cation, 1,3,4-trimethylimidazolium cation, 1-butyl-2,3-dimethylimidazolium cation, 1-butyl-3,4-dimethylimidazolium cation, 1-dodecyl-3,4-dimethylimidazolium cation, 1-dodecyl-2,3-dimethylimidazolium cation, 1-benzyl-3,4-dimethylimidazolium cation, 1-benzyl-2,3-dimethylimidazolium cation, 1-benzyl-3,4-dodecylimidazolium cation, 1-butyl-3,4-dipropylimidazolium cation, 1-dodecyl-3,4-dibutylimidazolium cation, 1-benzyl-3,4-hexadecylimidazolium cation or 1-benzyl-2,3-dibutylimidazolium cation;
[0017] The quaternary substituted imidazolium cation includes 1,3,4,5-tetramethylimidazolium cation, 1,4,5-trimethyl-3-butylimidazolium cation, 1-methyl-3,4,5-tributylimidazolium cation, 1-methyl-3,4,5-trihexylimidazolium cation or 1-methyl-4,5-dibutyl-3-hexylimidazolium cation.
[0018] Preferably, the mass of the imidazole ionic liquid is 1-20% of the mass of the prepolymer.
[0019] Preferably, the polymerization reaction temperature is 220-300° C., the reaction time is 4-20 h, the vacuum degree is 1-100000 Pa, and the stirring speed is 20-120 r / min.
[0020] The present invention provides ionic liquid grafted modified high temperature resistant bio-based nylon prepared by the preparation method described in the above technical scheme.
[0021] The present invention provides the application of the high temperature resistant bio-based nylon grafted with ionic liquid described in the above technical solution in the field of aerospace.
[0022] The present invention provides a preparation method of ionic liquid grafted modified high temperature resistant bio-based nylon, wherein after prepolymerization of nylon 5T salt, imidazole ionic liquid is added for final polymerization to obtain ionic liquid grafted modified high temperature resistant bio-based nylon. Different from the conventional melt copolymerization modification method, in the polymerization process of the present invention, the imidazole ionic liquid enters the polyamide macromolecular chain, which can reduce the intermolecular force and increase the molecular chain spacing, thereby reducing the melting point of the bio-based nylon, increasing the fluidity of the bio-based nylon, and improving the thermal properties and crystallization behavior of the bio-based nylon, thereby obtaining high-strength, high-oriented, and high-crystallization bio-based nylon.
[0023] Since the bio-based nylon prepared by the present invention has the characteristics of high strength, high orientation and high crystallinity, it can effectively improve the processing stability and spinning performance of the bio-based nylon in the later stage, and also reduce energy consumption. In addition, the anions and cations of the imidazole ionic liquids are highly designable, which provides a wide range of ideas for the design and synthesis of new functional high-temperature nylon. DETAILED DESCRIPTION
[0024] The present invention provides a method for preparing ionic liquid graft-modified high-temperature-resistant bio-based nylon, comprising the following steps:
[0025] mixing a bio-based nylon salt with water, mixing the obtained salt solution with an additive, and performing a prepolymerization reaction to obtain a prepolymer;
[0026] The prepolymer is mixed with an imidazole ionic liquid to carry out a polymerization reaction to obtain an ionic liquid graft-modified high-temperature-resistant bio-based nylon.
[0027] Unless otherwise specified, the raw materials or reagents used in the present invention are commercially available products well known in the art.
[0028] The invention mixes bio-based nylon salt with water, mixes the obtained salt solution with additives, performs prepolymerization reaction, and obtains a prepolymer.
[0029] In the present invention, the bio-based nylon salt preferably includes semi-aromatic bio-based nylon salt and / or aliphatic bio-based nylon salt; the semi-aromatic bio-based nylon salt preferably includes nylon 5T salt and / or nylon 5I salt; the aliphatic bio-based nylon salt preferably includes one or more of nylon 54 salt, nylon 56 salt and nylon 510 salt. When the bio-based nylon salt is two or more of the above, the present invention has no special limitation on the ratio of different types of nylon salts, and any ratio or adjustment according to actual needs can be used; in the embodiment of the present invention, the molar ratio of the two nylon salts is specifically 1:1.
[0030] The present invention has no particular limitation on the preparation method of the bio-based nylon salt. The corresponding bio-based nylon salt can be prepared using diamine and diacid according to methods well known in the art.
[0031] In the present invention, the method for preparing the bio-based nylon salt preferably comprises:
[0032] Under normal pressure and protective atmosphere, the diacid is dissolved in a solvent at 50-90° C. (more preferably 70-80° C.) to prepare an acid solution with a mass fraction of 30-80% (more preferably 40-70%, and further preferably 50-60%); at the same time, the bio-based diamine is dissolved in the same solvent at room temperature to prepare an amine solution with a mass fraction of 30-80% (more preferably 50-60%); the amine solution is added to the acid solution under stirring, so that the molar ratio of the amino group in the amine solution to the carboxyl group in the acid solution is 1-1.1:1 (more preferably 1-1.2:1). Preferably, the ratio of ...
[0033] In the present invention, the additives preferably include one or more of a catalyst, an antioxidant, an antistatic agent, a weathering agent, a capping agent, a nucleating agent, a flame retardant and a matting agent; when the mass of the additive is two or more of the above, the present invention has no special limitation on the ratio of different types of additives, which can be adjusted according to actual needs.
[0034] In the present invention, the mass of the additive is preferably 0.01 to 2.2 wt.% of the mass of the salt solution, and more preferably 0.3 to 0.7 wt.%.
[0035] In the present invention, the catalyst preferably includes one or more of anhydrous sodium hypophosphite, anhydrous potassium hypophosphite, anhydrous sodium phosphite and anhydrous potassium phosphite, and the addition amount (relative to the salt solution) is preferably 0.01-0.7wt.%; the antioxidant preferably includes antioxidant 1010 (tetrakis[3-3',5'-di-tert-butyl-4'-hydroxyphenyl]propionate butylpentaerythritol), antioxidant DLTDP (dilauryl thiodipropionate), antioxidant DSTDP (distearyl thiodipropionate), phenolic antioxidants, amine antioxidants. , phosphite antioxidants and thioester antioxidants; the phenolic antioxidants preferably include one or more of monophenol, bisphenol, triphenol, polyphenol, hydroquinone and thiobisphenol; the amine antioxidants preferably include one or more of naphthylamine, diphenylamine, p-phenylenediamine and quinoline; hindered phenolic antioxidants (1010, 1076) and amine antioxidants (naphthylamine, diphenylamine); the amount of the antioxidant added (relative to the salt solution) is preferably 0.01-0.1wt.%, more preferably 0.4-0.7wt.%. The end-capping agent preferably includes one or more of acetic acid, hexanoic acid, benzoic acid and hexylamine; the amount of the end-capping agent added (relative to the salt solution) is preferably 0.05-1.6wt.%.
[0036] In the present invention, the antistatic agent preferably includes one or more of quaternary phosphonium salt type cationic antistatic agent, quaternary ammonium salt type cationic antistatic agent and alkyl sulfate type anionic antistatic agent; the weathering agent preferably includes one or more of hydroquinone compounds, benzotriazole compounds and benzophenone compounds; the nucleating agent preferably includes one or more of silicon dioxide, clay, boron nitride, high melting point nylon and metal oxides; the flame retardant preferably includes one or more of magnesium hydroxide, brominated polystyrene, brominated polycarbonate and ammonium polyphosphate; the matting agent preferably includes titanium dioxide. The present invention has no special restrictions on the specific model of each additive, and the corresponding additives well known in the art can be used.
[0037] In the present invention, the mass fraction of the bio-based nylon salt in the salt solution is preferably 30 to 90%, more preferably 40 to 80%, and further preferably 50 to 70%.
[0038] The present invention preferably places bio-based nylon salt and water in a polymerization kettle, adds additives to the resulting salt solution, replaces the air in the kettle 5 times, stirs for 0.5 to 2 hours at 60 to 80° C. and 0.2 to 0.6 MPa in a protective atmosphere, more preferably at 70° C. and 0.3 to 0.5 MPa, stirs for 1.0 to 1.5 hours, heats up, and conducts a prepolymerization reaction; the gas used for the protective atmosphere is the same as above.
[0039] In the present invention, the temperature of the prepolymerization reaction is preferably 200-240°C, more preferably 210-220°C, the pressure is preferably 1.5-2.3 MPa, more preferably 1.7-2.1 MPa, further preferably 1.8-2.0 MPa, and the time is 0.5-5 h, more preferably 1-4 h, further preferably 2-3 h.
[0040] After the prepolymerization reaction is completed, the present invention preferably reduces the pressure to 0.001-0.01Mpa so that more than 98% of the water in the system is discharged; after cooling, the obtained prepolymer is crushed, washed with anhydrous ethanol, and dried (to remove residual nylon salt, monomer, small molecule oligomer impurities) to obtain a prepolymer powder; the drying method is preferably one or more of vacuum drying, freeze drying, air flow drying, microwave drying, infrared drying and high frequency drying.
[0041] After obtaining the prepolymer, the present invention mixes the prepolymer with an imidazole ionic liquid to carry out a polymerization reaction to obtain the ionic liquid graft-modified high-temperature-resistant bio-based nylon.
[0042] In the present invention, the anion of the imidazolium-based ionic liquid preferably includes one of a halogen ion, an inorganic acid radical ion, a carboxylate ion and a sulfonate ion.
[0043] In the present invention, the halogen ion is preferably a fluoride ion, a chloride ion or a bromide ion; the inorganic acid ion preferably includes a sulfate ion, a hydrogen sulfate ion, a carbonate ion, a phosphate ion, a dihydrogen phosphate ion, a dihydrogen phosphate ion, a borate ion, a nitrate ion, a hexafluorophosphate ion or a tetrafluoroborate ion; the carboxylate ion preferably includes an acetate ion, a propionate ion or a butyrate ion; the sulfonate ion preferably includes a methanesulfonate ion, a toluenesulfonate ion or a trifluoromethylsulfonate ion;
[0044] The anions of the imidazolium ionic liquid preferably also include diethyl phosphate ions, ethyl sulfate ions, ethyl sulfonate ions, bis(2,4,4-trimethylpentyl)phosphinate ions, bis(trifluoromethanesulfonyl)methane ions, bis(malonate)borate ions, bis(pentafluoroethyl)phosphinate ions, tetrakis(methylsulfate)borate ions or bis(salicylate)borate ions.
[0045] In the present invention, the cation of the imidazolium ionic liquid preferably includes one of a di-substituted imidazolium cation, a ternary substituted imidazolium cation and a quaternary substituted imidazolium cation;
[0046] The disubstituted imidazolium cation preferably includes 1,3-dimethylimidazolium cation, 1-butyl-3-methylimidazolium cation, 1-ethyl-3-methylimidazolium cation, 1-octyl-3-methylimidazolium cation, 1-allyl-3-methylimidazolium cation, 1-butyl-3-ethylimidazolium cation, 1-benzyl-3-methylimidazolium cation, 1-dodecyl-3-methylimidazolium cation, 1-hexadecyl-3-methylimidazolium cation, 1-eicosyl-3-methylimidazolium cation, N-methylimidazolium cation, N-butylimidazolium cation or N-dodecylimidazolium cation;
[0047] The ternary substituted imidazolium cation includes 1,2,3-trimethylimidazolium cation, 1,3,4-trimethylimidazolium cation, 1-butyl-2,3-dimethylimidazolium cation, 1-butyl-3,4-dimethylimidazolium cation, 1-dodecyl-3,4-dimethylimidazolium cation, 1-dodecyl-2,3-dimethylimidazolium cation, 1-benzyl-3,4-dimethylimidazolium cation, 1-benzyl-2,3-dimethylimidazolium cation, 1-benzyl-3,4-dodecylimidazolium cation, 1-butyl-3,4-dipropylimidazolium cation, 1-dodecyl-3,4-dibutylimidazolium cation, 1-benzyl-3,4-hexadecylimidazolium cation or 1-benzyl-2,3-dibutylimidazolium cation;
[0048] The quaternary substituted imidazolium cation includes 1,3,4,5-tetramethylimidazolium cation, 1,4,5-trimethyl-3-butylimidazolium cation, 1-methyl-3,4,5-tributylimidazolium cation, 1-methyl-3,4,5-trihexylimidazolium cation or 1-methyl-4,5-dibutyl-3-hexylimidazolium cation.
[0049] In the present invention, the imidazole ionic liquid is preferably 1-butyl-3-methylimidazolium chloride (BMIMCl), 1-allyl-3-methylimidazolium chloride (AMIMCl), 1-butyl-3-methylimidazolium tetrafluoroborate (BMIM·BF4), 1-butyl-3-methylimidazolium hexafluorophosphate (BMIM·PF6), 1-hexadecyl-3-methylimidazolium bromide (C 16 MIMBr), 1-butyl-3-methylimidazolium bromide (BMIMBr).
[0050] In the present invention, the mass of the imidazolium-based ionic liquid is preferably 1 to 20% of the mass of the prepolymer, more preferably 5 to 15%, and even more preferably 6 to 12%.
[0051] The present invention preferably adds prepolymer powder and imidazole ionic liquid into a polymerization kettle, stirs and heats to the polymerization reaction temperature under a protective atmosphere, then performs negative pressure polymerization (to avoid blockage of vacuum pipes), cools to room temperature, and discharges the material to obtain ionic liquid grafted modified high temperature resistant bio-based nylon.
[0052] In the present invention, the gas used for the protective atmosphere preferably includes at least one of nitrogen, argon, helium and carbon dioxide, more preferably at least one of nitrogen, argon and helium, and further preferably nitrogen and argon.
[0053] In the present invention, the polymerization reaction temperature is preferably 220-300°C, more preferably 240-260°C, the time is preferably 4-20h, more preferably 5-15h, further preferably 6-12h, the vacuum degree is preferably 1-100000Pa, more preferably 800-1000Pa, the stirring speed is preferably 20-120r / min, more preferably 40-100r / min, further preferably 50-80r / min.
[0054] After the polymerization reaction is completed, the present invention preferably cools naturally to room temperature and discharges the material to obtain ionic liquid grafted modified high temperature resistant bio-based nylon.
[0055] The present invention provides ionic liquid grafted modified high temperature resistant bio-based nylon prepared by the preparation method described in the above technical scheme.
[0056] The present invention provides the application of the ionic liquid grafted modified high temperature resistant bio-based nylon in the aerospace field. The present invention has no special limitation on the application method, and the application can be carried out according to the method known in the art.
[0057] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0058] Example 1
[0059] Under normal pressure and nitrogen purge conditions, 73.0174g of phthalic acid was weighed and dissolved in pure water at 70°C to prepare a turbid phthalic acid suspension with a mass fraction of 40%; at the same time, 44.9101g of pentamethylenediamine was weighed and dissolved in pure water at room temperature to prepare a clear pentamethylenediamine solution with a mass fraction of 60%; then, the pentamethylenediamine solution was added to the phthalic acid solution under stirring conditions of 300r / min (the molar ratio of carboxyl group to amine group was 1:1), the temperature was maintained at 70°C, and after continuous stirring for 2h, the obtained mixed solution was cooled to 4°C and allowed to stand for 3h, and the precipitated crystals were filtered, washed, and dried to obtain nylon 5I salt; according to the above reaction steps, succinic acid and pentamethylenediamine were used as reaction monomers (the molar ratio of carboxyl group to amine group was 1:1.02) to obtain nylon 54 salt;
[0060] A total of 113.09 g of dried nylon 5I salt and nylon 54 salt (molar ratio 1:1) were weighed and put into a 1L stainless steel autoclave, 75.39 g of pure water was added to make the mass fraction of nylon salt 60%, and then 0.9304 g of catalyst anhydrous sodium hypophosphite and 0.1507 g of antioxidant 1010 were added. After nitrogen replaced the air in the autoclave 5 times, the mixture was stirred at 80° C. and 0.5 MPa nitrogen atmosphere for 1.5 h to completely dissolve the nylon salt; the temperature was raised to 200° C. and the pressure was raised to 2.0 MPa to carry out prepolymerization for 4 h; then the pressure was reduced to 0.001 MPa to discharge more than 98% of the water in the system, and the nylon 5I / 54 prepolymer was obtained after cooling;
[0061] The above prepolymer was crushed, washed with anhydrous ethanol and vacuum dried, and the obtained prepolymer powder and 1-butyl-3-methylimidazole chloride (BMIMCl) accounting for 10% of the mass of the prepolymer were added to a polymerization kettle. After heating to 240°C at 50 r / min under nitrogen purge, the vacuum was evacuated to 800 Pa, and the mixture was kept warm for 4 hours. The heating was stopped, the mixture was naturally cooled to room temperature, and the material was discharged to obtain high-temperature resistant bio-based nylon 5I / 54.
[0062] Example 2
[0063] Under normal pressure and argon purging conditions, 72.8164g of terephthalic acid was weighed and dissolved in pure water at 80°C to prepare a turbid terephthalic acid suspension with a mass fraction of 60%; at the same time, 49.2673g of pentamethylenediamine was weighed and dissolved in pure water at room temperature to prepare a clear pentamethylenediamine solution with a mass fraction of 40%; then, the pentamethylenediamine solution was added to the terephthalic acid solution under stirring conditions of 300r / min (the molar ratio of carboxyl group to amine group was 1:1.1), the temperature was maintained at 80°C, and after continuous stirring for 1h, the obtained mixed solution was cooled to 8°C and allowed to stand for 2h, and the precipitated crystals were filtered, washed, and dried to obtain nylon 5T salt; according to the above reaction steps, succinic acid and pentamethylenediamine were used as reaction monomers (the molar ratio of carboxyl group to amine group was 1:1.1) to obtain nylon 54 salt;
[0064] Weigh a total of 125.63 g of dried nylon 5T salt and nylon 54 salt (molar ratio 1:1) into a 1L stainless steel autoclave, add 290.17 g of pure water to make the mass fraction of nylon salt 30%, then add 1.0577 g of anhydrous sodium hypophosphite as a catalyst and 0.2104 g of end-capping agent benzoic acid, replace the air in the autoclave with argon for 5 times, stir for 2 h at 80 ° C and 0.5 MPa argon atmosphere to completely dissolve the nylon salt; raise the temperature to 210 ° C and the pressure to 2.1 MPa to carry out prepolymerization for 3 h; then reduce the pressure to 0.001 MPa to discharge more than 98% of the water in the system, and cool down to obtain a nylon 5T / 54 prepolymer;
[0065] The above prepolymer was crushed, washed with anhydrous ethanol, and freeze-dried. The obtained prepolymer powder and 1-allyl-3-methylimidazole chloride (AMIMCl) accounting for 5% of the mass of the prepolymer were added to a polymerization kettle. Under argon purge, the temperature was heated to 260°C at 20 r / min while stirring, and then evacuated to a vacuum degree of 1000 Pa. The mixture was kept warm for 5 hours, and the heating was stopped. The mixture was naturally cooled to room temperature. After discharging, high-temperature resistant bio-based nylon 5T / 54 was obtained.
[0066] Example 3
[0067] Under normal pressure and nitrogen purge conditions, 72.5089g of phthalic acid was weighed and dissolved in pure water at 70°C to prepare a turbid phthalic acid suspension with a mass fraction of 50%; at the same time, 47.6359g of pentamethylenediamine was weighed and dissolved in pure water at room temperature to prepare a clear pentamethylenediamine solution with a mass fraction of 50%; then, the pentamethylenediamine solution was added to the phthalic acid solution under stirring conditions of 300r / min (the molar ratio of carboxyl group to amine group was 1:1.07), the temperature was maintained at 70°C, and stirring was continued for 2.5h, and the obtained mixed solution was cooled to 4°C and allowed to stand for 3h. The precipitated crystals were filtered, washed, and dried to obtain nylon 5I salt; according to the above reaction steps, adipic acid and pentamethylenediamine were used as reaction monomers (the molar ratio of carboxyl group to amine group was 1:1.04) to obtain nylon 56 salt;
[0068] A total of 123.05 g of dried nylon 5I salt and nylon 56 salt (molar ratio 1:1) were weighed and put into a 1L stainless steel autoclave, 185.37 g of pure water was added to make the mass fraction of nylon salt 40%, and then 1.4427 g of catalyst anhydrous potassium hypophosphite and 0.1532 g of antioxidant 1076 were added. After nitrogen replaced the air in the autoclave 5 times, the mixture was stirred at 80° C. and 0.5 MPa nitrogen atmosphere for 2 h to completely dissolve the nylon salt; the temperature was raised to 220° C. and the pressure was raised to 1.5 MPa to carry out prepolymerization for 4 h; then the pressure was reduced to 0.001 MPa to discharge more than 98% of the water in the system, and the nylon 5I / 56 prepolymer was obtained after cooling;
[0069] The above prepolymer was crushed, washed with anhydrous ethanol, and microwave dried. The obtained prepolymer powder and 1-butyl-3-methylimidazolium tetrafluoroborate (BMIM·BF4) accounting for 15% of the mass of the prepolymer were added to a polymerization kettle. The temperature was raised to 260°C at 80r / min while stirring under nitrogen purge, and then evacuated to a vacuum degree of 600Pa. The mixture was kept warm for 10 hours, and the heating was stopped. The mixture was naturally cooled to room temperature. After discharging, high-temperature resistant bio-based nylon 5I / 56 was obtained.
[0070] Example 4
[0071] Under normal pressure and nitrogen purge conditions, 74.7054 g of terephthalic acid was weighed and dissolved in pure water at 70° C. to prepare a turbid terephthalic acid suspension with a mass fraction of 50%; at the same time, 46.8487 g of pentamethylenediamine was weighed and dissolved in pure water at room temperature to prepare a clear pentamethylenediamine solution with a mass fraction of 50%; then, the pentamethylenediamine solution was added to the terephthalic acid solution under stirring conditions of 300 r / min (the molar ratio of carboxyl group to amine group was 1:1.02), the temperature was maintained at 80° C., and after continuous stirring for 2 hours, the obtained mixed solution was cooled to 4° C. and allowed to stand for 3 hours. The precipitated crystals were filtered, washed, and dried to obtain nylon 5T salt; according to the above reaction steps, adipic acid and pentamethylenediamine were used as reaction monomers (the molar ratio of carboxyl group to amine group was 1:1.02) to obtain nylon 56 salt;
[0072] Weigh a total of 141.07 g of dried nylon 5T salt and nylon 56 salt (molar ratio 1:1) and put them into a 1L stainless steel autoclave, add 60.28 g of pure water to make the mass fraction of nylon salt 70%, then add 1.3287 g of catalyst anhydrous potassium hypophosphite and 0.1503 g of antioxidant 1076, replace the air in the autoclave with nitrogen for 5 times, stir for 2 hours at 80°C and 0.5 MPa nitrogen atmosphere to completely dissolve the nylon salt; raise the temperature to 230°C and the pressure to 1.6 MPa to carry out prepolymerization for 5 hours; then reduce the pressure to 0.001 MPa to discharge more than 98% of the water in the system, and cool to obtain nylon 5T / 56 prepolymer;
[0073] The above prepolymer was crushed, washed with anhydrous ethanol and vacuum dried, and the obtained prepolymer powder and 1-butyl-3-methylimidazolium hexafluorophosphate (BMIM·PF6) accounting for 12% of the mass of the prepolymer were added to a polymerization kettle. The temperature was raised to 280°C at 50r / min while stirring under nitrogen purge, and then evacuated to a vacuum degree of 1200Pa. The mixture was kept warm for 12h, and the heating was stopped. The mixture was naturally cooled to room temperature. After discharging, high-temperature resistant bio-based nylon 5T / 56 was obtained.
[0074] Example 5
[0075] Under normal pressure and nitrogen purge conditions, 75.0037g of phthalic acid was weighed and dissolved in pure water at 50°C to prepare a turbid phthalic acid suspension with a mass fraction of 70%; at the same time, 48.8933g of pentamethylenediamine was weighed and dissolved in pure water at room temperature to prepare a clear pentamethylenediamine solution with a mass fraction of 30%; then, the pentamethylenediamine solution was added to the phthalic acid solution under stirring conditions of 300r / min (the molar ratio of carboxyl group to amine group was 1:1.06), the temperature was maintained at 50°C, and after continuous stirring for 2h, the obtained mixed solution was cooled to 4°C and allowed to stand for 3h, and the precipitated crystals were filtered, washed, and dried to obtain nylon 5I salt; according to the above reaction steps, sebacic acid and pentamethylenediamine were used as reaction monomers (the molar ratio of carboxyl group to amine group was 1:1.06) to obtain nylon 510 salt;
[0076] Weigh a total of 131.07 g of dried nylon 5I salt and nylon 510 salt (molar ratio 1:1) and put them into a 1L stainless steel autoclave, add 15.21 g of pure water to make the mass fraction of nylon salt 90%, then add 0.1552 g of anhydrous potassium phosphite as a catalyst and 0.1073 g of naphthylamine as an antioxidant, replace the air in the autoclave with nitrogen for 5 times, stir for 2 h at 80° C. and 0.5 MPa of nitrogen atmosphere to completely dissolve the nylon salt; raise the temperature to 240° C. and the pressure to 1.7 MPa to carry out prepolymerization for 2 h; then reduce the pressure to 0.001 MPa to discharge more than 98% of the water in the system, and cool down to obtain a nylon 5I / 510 prepolymer;
[0077] The prepolymer was crushed, washed with anhydrous ethanol, and dried in vacuo. The obtained prepolymer powder and 1-hexadecyl-3-methylimidazolium bromide (C 16 MIMBr) was added into the polymerization kettle, and the temperature was raised to 270°C at 120 r / min while stirring under nitrogen purge, and then evacuated to a vacuum degree of 800 Pa, and kept warm for 20 hours. The heating was stopped, and the mixture was naturally cooled to room temperature. After discharging, high-temperature resistant bio-based nylon 5I / 510 was obtained.
[0078] Example 6
[0079] Under normal pressure and argon purging conditions, 77.0009g of terephthalic acid was weighed and dissolved in pure water at 90°C to prepare a turbid terephthalic acid suspension with a mass fraction of 30%; at the same time, 47.5249g of pentamethylenediamine was weighed and dissolved in pure water at room temperature to prepare a clear pentamethylenediamine solution with a mass fraction of 80%; then, the pentamethylenediamine solution was added to the terephthalic acid solution under stirring conditions of 300r / min (the molar ratio of carboxyl group to amine group was 1:1), the temperature was maintained at 90°C, and after continuous stirring for 2h, the obtained mixed solution was cooled to 4°C and allowed to stand for 3h, and the precipitated crystals were filtered, washed, and dried to obtain nylon 5T salt; according to the above reaction steps, sebacic acid and pentamethylenediamine were used as reaction monomers (the molar ratio of carboxyl group to amine group was 1:1) to obtain nylon 510 salt;
[0080] Weigh a total of 109.08 g of dried nylon 5T salt and nylon 510 salt (molar ratio 1:1) into a 1L stainless steel autoclave, add 163.60 g of pure water to make the mass fraction of nylon salt 40%, then add 1.5057 g of anhydrous sodium phosphite as a catalyst and 4.3107 g of end-capping agent hexylamine, replace the air in the autoclave with argon gas 5 times, stir for 1.5 h at 80 ° C and 0.5 MPa argon atmosphere to completely dissolve the nylon salt; raise the temperature to 240 ° C and the pressure to 1.8 MPa to carry out prepolymerization for 5 h; then reduce the pressure to 0.001 MPa to discharge more than 98% of the water in the system, and cool down to obtain a nylon 5T / 510 prepolymer;
[0081] The above prepolymer was crushed, washed with anhydrous ethanol and freeze-dried, and the obtained prepolymer powder and 14% of the mass of the prepolymer 1-butyl-3-methylimidazolium bromide (BMIMBr) were added to a polymerization kettle. The mixture was heated to 300°C at 100 r / min under argon purge, and then evacuated to a vacuum degree of 1000 Pa. The mixture was kept warm for 15 hours, and the heating was stopped. The mixture was naturally cooled to room temperature. After discharging, high-temperature resistant bio-based nylon 5T / 510 was obtained.
[0082] Comparative Example 1
[0083] Under normal pressure and nitrogen purge conditions, 70.3881 g of terephthalic acid was weighed and dissolved in pure water at 70° C. to prepare a turbid terephthalic acid suspension with a mass fraction of 50%; at the same time, 44.1815 g of pentamethylenediamine was weighed and dissolved in pure water at room temperature to prepare a clear pentamethylenediamine solution with a mass fraction of 50%; then, the pentamethylenediamine solution was added to the terephthalic acid solution under stirring conditions of 300 r / min (the molar ratio of carboxyl group to amine group was 1:1.02), the temperature was maintained at 80° C., and after continuous stirring for 2 hours, the obtained mixed solution was cooled to 4° C. and allowed to stand for 3 hours. The precipitated crystals were filtered, washed, and dried to obtain nylon 5T salt; according to the above reaction steps, adipic acid and pentamethylenediamine were used as reaction monomers (the molar ratio of carboxyl group to amine group was 1:1.02) to obtain nylon 56 salt;
[0084] A total of 121.17 g of dried nylon 5T salt and nylon 56 salt (molar ratio 1:1) were weighed and put into a 1L stainless steel autoclave, 52.01 g of pure water was added to make the mass fraction of nylon salt 70%, and then 1.0057 g of anhydrous potassium hypophosphite as a catalyst and 0.1216 g of antioxidant 1076 were added. After nitrogen replaced the air in the autoclave 5 times, the mixture was stirred at 80° C. and 0.5 MPa in an inert atmosphere for 2 h to completely dissolve the nylon salt; the temperature was raised to 230° C. and the pressure was raised to 1.6 MPa to carry out a prepolymerization reaction for 5 h; then the pressure was reduced to 0.001 MPa to discharge more than 98% of the water in the system, and the nylon 5T / 56 prepolymer was obtained after cooling;
[0085] The above prepolymer was crushed, washed with anhydrous ethanol, and vacuum dried. The obtained prepolymer powder was added into a polymerization kettle. After heating to 280°C at 50 r / min with stirring under nitrogen purge, the mixture was evacuated to a vacuum degree of 1200 Pa and kept warm for 12 hours. The heating was stopped and the mixture was naturally cooled to room temperature. After discharging, high-temperature resistant bio-based nylon 5T / 56 was obtained.
[0086] Comparative Example 2
[0087] Under normal pressure and nitrogen purge conditions, 76.5027g of phthalic acid was weighed and dissolved in pure water at 50°C to prepare a turbid phthalic acid suspension with a mass fraction of 70%; at the same time, 49.6911g of pentamethylenediamine was weighed and dissolved in pure water at room temperature to prepare a clear pentamethylenediamine solution with a mass fraction of 30%; then, the pentamethylenediamine solution was added to the phthalic acid solution (the molar ratio of carboxyl group to amine group was 1:1.06) under stirring at 300r / min, the temperature was maintained at 50°C, and after continuous stirring for 2h, the obtained mixed solution was cooled to 4°C and allowed to stand for 3h. The precipitated crystals were filtered, washed, and dried to obtain nylon 5I salt; according to the above reaction steps, sebacic acid and pentamethylenediamine were used as reaction monomers (the molar ratio of carboxyl group to amine group was 1:1.06) to obtain nylon 510 salt;
[0088] Weigh a total of 108.27 g of dried nylon 5I salt and nylon 510 salt (molar ratio 1:1) and put them into a 1L stainless steel autoclave, add 12.21 g of pure water to make the mass fraction of nylon salt 90%, then add 0.1507 g of anhydrous potassium phosphite as a catalyst and 0.1106 g of naphthylamine as an antioxidant, replace the air in the autoclave with nitrogen for 5 times, stir for 2 hours at 80° C. and 0.5 MPa in an inert atmosphere to completely dissolve the nylon salt; raise the temperature to 240° C. and the pressure to 1.7 MPa to carry out a prepolymerization reaction for 2 hours; then reduce the pressure to 0.001 MPa to discharge more than 98% of the water in the system, and cool down to obtain a nylon 5I / 510 prepolymer;
[0089] The above prepolymer was crushed, washed with anhydrous ethanol, and vacuum dried. The obtained prepolymer powder was added into a polymerization kettle. After heating to 270°C at 120 r / min under nitrogen purge, the mixture was evacuated to a vacuum degree of 800 Pa and kept warm for 20 hours. The heating was stopped and the mixture was naturally cooled to room temperature. After discharging, high-temperature resistant bio-based nylon 5I / 510 was obtained.
[0090] Performance Testing
[0091] 1) The properties of the nylon polymers obtained in Examples 1 to 6 and Comparative Examples 1 to 2 were tested. The test results are shown in Table 1.
[0092] The test standards for each indicator are as follows:
[0093] Relative viscosity test: Nylon polymer was dissolved in 96% concentrated sulfuric acid to prepare a 0.01 g / mL solution. The outflow time of the solution t1 and the pure solvent t0 was measured with an Ubbelohde viscometer at a temperature of 25°C. The relative viscosity of the sample was calculated by t1 / t0.
[0094] GPC analysis: Molecular weight and distribution were determined by gel permeation chromatography using hexafluoroisopropanol as mobile phase and RI-UV as detector.
[0095] DSC analysis: Under nitrogen atmosphere, the temperature was raised from room temperature to 350°C at a heating and cooling rate of 10°C / min, kept constant for 3 min, then dropped to room temperature and then raised to 350°C.
[0096] TG analysis: Under nitrogen conditions, the temperature was increased from room temperature to 800°C at a heating rate of 10°C / min.
[0097] Yellowness index: measured according to HG / T 3862-2006 method.
[0098] Mechanical properties: All tests were carried out at a temperature of 25°C and a relative humidity of 75%. The tensile properties were tested according to GB / T1040-2006 with a tensile rate of 20 mm / min. The bending properties were tested according to GB / T9341-2008 with a span of 64 mm and a rate of 2 mm / min. The simply supported beam impact properties were tested according to GB / T1043-2008 without a notch.
[0099] Table 1 Performance data of nylon polymers in Examples 1 to 6 and Comparative Examples 1 to 2
[0100]
[0101] It can be seen from Table 1 that, compared with Example 4, Comparative Example 1 and Example 5, Comparative Example 2 can be compared with Example 5, and compared with the case without adding ionic liquid, the present invention adds ionic liquid in the final polymerization process, which can reduce the intermolecular force and increase the molecular chain spacing, thereby reducing the melting point of bio-based nylon, increasing the fluidity of bio-based nylon, improving the thermal properties, crystallization and other behaviors of bio-based nylon, effectively improving the processing stability and spinning performance of bio-based nylon in the later stage, and reducing energy consumption, thereby obtaining high-strength, high-oriented, and high-crystalline bio-based nylon (high crystallization temperature indicates high crystallization, and high toughness and strength of the polymer indicate high orientation).
[0102] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing high temperature resistant bio-based nylon grafted with ionic liquid, comprising the following steps: mixing a bio-based nylon salt with water, mixing the obtained salt solution with an additive, and performing a prepolymerization reaction to obtain a prepolymer; The prepolymer is mixed with an imidazole ionic liquid to carry out a polymerization reaction to obtain an ionic liquid graft-modified high-temperature-resistant bio-based nylon.
2. The preparation method according to claim 1, characterized in that: The bio-based nylon salt includes semi-aromatic bio-based nylon salt and / or aliphatic bio-based nylon salt; the semi-aromatic bio-based nylon salt includes nylon 5T salt and / or nylon 5I salt; the aliphatic bio-based nylon salt includes one or more of nylon 54 salt, nylon 56 salt and nylon 510 salt; the mass fraction of the bio-based nylon salt in the salt solution is 30-90%.
3. The preparation method according to claim 1, characterized in that: The additives include one or more of a catalyst, an antioxidant, an antistatic agent, a weathering agent, a capping agent, a nucleating agent, a flame retardant and a matting agent; the mass of the additives is 0.01-2.2wt.% of the mass of the salt solution.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The prepolymerization reaction is carried out at a temperature of 200 to 240° C., a pressure of 1.5 to 2.3 MPa, and a time of 0.5 to 5 hours.
5. The preparation method according to claim 1, characterized in that: The anions of the imidazole ionic liquid include one of halogen ions, inorganic acid radical ions, carboxylate ions and sulfonate ions; the cations of the imidazole ionic liquid include one of disubstituted imidazole cations, ternary substituted imidazole cations and quaternary substituted imidazole cations.
6. The preparation method according to claim 5, characterized in that: The halogen ion is a fluoride ion, a chloride ion or a bromide ion; the inorganic acid ion includes a sulfate ion, a hydrogen sulfate ion, a carbonate ion, a phosphate ion, a dihydrogen phosphate ion, a dihydrogen phosphate ion, a borate ion, a nitrate ion, a hexafluorophosphate ion or a tetrafluoroborate ion; the carboxylate ion includes an acetate ion, a propionate ion or a butyrate ion; the sulfonate ion includes a methanesulfonate ion, a toluenesulfonate ion or a trifluoromethylsulfonate ion; The anions of the imidazole ionic liquid also include diethyl phosphate ions, ethyl sulfate ions, ethyl sulfonate ions, bis(2,4,4-trimethylpentyl)phosphinate ions, bis(trifluoromethanesulfonyl)methane ions, bis(malonate)borate ions, bis(pentafluoroethyl)phosphinate ions, tetrakis(methylsulfate)borate ions or bis(salicylate)borate ions; The dibasic substituted imidazolium cation includes 1,3-dimethylimidazolium cation, 1-butyl-3-methylimidazolium cation, 1-ethyl-3-methylimidazolium cation, 1-octyl-3-methylimidazolium cation, 1-allyl-3-methylimidazolium cation, 1-butyl-3-ethylimidazolium cation, 1-benzyl-3-methylimidazolium cation, 1-dodecyl-3-methylimidazolium cation, 1-hexadecyl-3-methylimidazolium cation, 1-eicosyl-3-methylimidazolium cation, N-methylimidazolium cation, N-butylimidazolium cation or N-dodecylimidazolium cation; The ternary substituted imidazolium cation includes 1,2,3-trimethylimidazolium cation, 1,3,4-trimethylimidazolium cation, 1-butyl-2,3-dimethylimidazolium cation, 1-butyl-3,4-dimethylimidazolium cation, 1-dodecyl-3,4-dimethylimidazolium cation, 1-dodecyl-2,3-dimethylimidazolium cation, 1-benzyl-3,4-dimethylimidazolium cation, 1-benzyl-2,3-dimethylimidazolium cation, 1-benzyl-3,4-dodecylimidazolium cation, 1-butyl-3,4-dipropylimidazolium cation, 1-dodecyl-3,4-dibutylimidazolium cation, 1-benzyl-3,4-hexadecylimidazolium cation or 1-benzyl-2,3-dibutylimidazolium cation; The quaternary substituted imidazolium cation includes 1,3,4,5-tetramethylimidazolium cation, 1,4,5-trimethyl-3-butylimidazolium cation, 1-methyl-3,4,5-tributylimidazolium cation, 1-methyl-3,4,5-trihexylimidazolium cation or 1-methyl-4,5-dibutyl-3-hexylimidazolium cation.
7. The preparation method according to claim 6, characterized in that: The mass of the imidazole ionic liquid is 1-20% of the mass of the prepolymer.
8. The preparation method according to claim 1, characterized in that: The polymerization reaction temperature is 220-300° C., the reaction time is 4-20 hours, the vacuum degree is 1-100000 Pa, and the stirring speed is 20-120 r / min.
9. The high temperature resistant bio-based nylon grafted and modified by the preparation method according to any one of claims 1 to 8.
10. Application of the high temperature resistant bio-based nylon grafted with ionic liquid as claimed in claim 9 in the aerospace field.
Citation Information
Patent Citations
Preparation of polyamides
CN102471484A
High-temperature-resistant semi-aromatic polymer and preparation method thereof
CN112280031A
Imidazolium ionic liquid toughened and modified nylon 6 as well as preparation and application thereof
CN117965019A
Preparation method of bio-based semi-aromatic high-temperature-resistant nylon PA5T / 56
CN118325071A
Method for producing polyamides
US20100311918A1
Cited By
Ternary copolymerized nylon resin as well as preparation method and application thereof
CN120173236A